2004
DOI: 10.1002/jpln.200321175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water and nitrogen management on aggregate size and carbon enrichment of soil in rice‐wheat cropping system

Abstract: A study was carried out on a silty clay loam soil (Typic Haplustept) to evaluate the effect of farmyard manure (FYM) vis-à-vis fertilizer and irrigation application on the soil organic C content and soil structure. The fertilizer treatments comprised of eight different combinations of N and FYM and three water regimes. The results indicated that the application of FYM and increasing N rate increased soil organic carbon (SOC) content. Addition of FYM also increased the percentage of large sized water stable agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Emerson (1977) suggested that SOM stabilized the aggregates mainly by forming and strengthening bonds between the particles within them. The effect of increasing SOC content in larger size fractions has been reported by many workers in different soil management systems (Cambardella and Elliott 1994;Monreal et al 1995;Six et al 1998;Tripathi and Singh 2004). Like us, Cambardella and Elliott (1994) reported higher organic C density in macroaggregates (1,600 g m -2 ) compared to microaggregates (800 g m -2 in 0.053-mm fraction and 600 g m -2 in \0.053 mm fraction).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Emerson (1977) suggested that SOM stabilized the aggregates mainly by forming and strengthening bonds between the particles within them. The effect of increasing SOC content in larger size fractions has been reported by many workers in different soil management systems (Cambardella and Elliott 1994;Monreal et al 1995;Six et al 1998;Tripathi and Singh 2004). Like us, Cambardella and Elliott (1994) reported higher organic C density in macroaggregates (1,600 g m -2 ) compared to microaggregates (800 g m -2 in 0.053-mm fraction and 600 g m -2 in \0.053 mm fraction).…”
Section: Discussionsupporting
confidence: 49%
“…Comparison of SOC content in different sized water stable aggregate classes shows that macroaggregates ([0.25 mm) are the main source of highly enriched fractions of SOC (Cambardella and Elliott 1994) with wider C:N ratios (Whalen et al 2003). Storage of organic C in macroaggregates thus deserves detailed study, so enable increased labile and protected SOC and reduce CO 2 emissions (Tripathi and Singh 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of Mulumba et al [25], who stated that long-term residue incorporation has increasingly positive impacts on soil porosity. Previous studies also found that soil porosity increased by 5.5% at soil depths of 0-30 cm, with straw incorporation practices compared with traditional methods [26,27]. Additionally, Zhang et al [28] reported that straw incorporation increased the SOC concentration and reduced bulk density, thereby improving total porosity, aeration, and water-holding capacity.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies by Tripathy et al [27], Karami et al [43], and Memon et al [49] showed that straw incorporation is a key management strategy to enhance crop production, along with improved soil fertility and water availability [50]. Additionally, straw incorporation decreases the un-productive component of evapotranspiration and creates favorable root environment by improving soil structure, which provides a clean, uniform seedbed that facilitates crop establishment [51].…”
Section: Discussionmentioning
confidence: 99%
“…The added organics could supply additional fresh organic residues (water soluble and hydrolysable substrates) and C to the soil resulting in production of microbial polysaccharides that increase aggregate cohesion which could explain the observed progressive increase in aggregate stability to mechanical breakdown. Positive effects of manure and straw application on aggregate stability have been reported in a number of studies (Tripathy and Singh, 2004;Singh et al, 2007). Shattering of macroaggregates and breaking up of roots and fungal hyphae as a result of tillage even annual applications of FYM, PS and GM for 21 years could reduce MWD, GMD and aggregate stability.…”
Section: Carbon Inputs and Soil Aggregationmentioning
confidence: 94%